2015
DOI: 10.1002/jhbp.256
|View full text |Cite
|
Sign up to set email alerts
|

Cholangiocyte senescence caused by lysophosphatidylcholine as a potential implication in carcinogenesis

Abstract: Based on these data, cholangiocyte senescence and SASP caused by LPC are potential pathogenic mechanisms in the development of biliary tract cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 31 publications
(44 reference statements)
0
29
0
Order By: Relevance
“…Therefore, LPC may be a novel biomarker allowing early detection of biliary tract cancer [ 30 ]. Recent studies have shown that LPC may trigger cholangiocyte senescence, thereby potentially contributing to the pathogenic development of biliary tract cancer [ 42 ]. LPC also inhibited cholangiocyte apoptosis by inducing COX-2 expression via a Raf-1-dependent mechanism [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, LPC may be a novel biomarker allowing early detection of biliary tract cancer [ 30 ]. Recent studies have shown that LPC may trigger cholangiocyte senescence, thereby potentially contributing to the pathogenic development of biliary tract cancer [ 42 ]. LPC also inhibited cholangiocyte apoptosis by inducing COX-2 expression via a Raf-1-dependent mechanism [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sources of ROS in endothelial cells are derived mainly from NADPH oxidase, xanthine oxidase, arachidonic acid (AA) metabolism or mitochondrial electron transfer. LPC has been shown to be the ROS inducer in endothelial cells [ 12 15 ] and may induce oxidative DNA damage and gene hypomethylation in cholangiocytes [ 16 ]. ROS and DNA damage may stimulate ataxia-telangiectasia mutated (ATM)/checkpoint kinase-1 (Chk2) and ATM and RAD3-related (ATR)/Chk1 to regulate cell cycle progression and induce apoptosis [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to our previous finding that PC inhibits cholangiocyte damage in response to LPC, accumulating reports have revealed the biological properties of PC, including its anti-inflammatory and anti-oxidant activities [9,23]. Indeed, PC plays a rate-limiting role in the activation of numerous membrane-located enzymes, including superoxide dismutase and glutathione, important antioxidants that protect cellular membranes from ROS damage [24].…”
Section: Discussionmentioning
confidence: 99%
“…Lysophosphatidylcholine is produced from phosphatidylcholine (PC) through the hydrolysis of phospholipase A2 (PLA2), which is caused by the entry of pancreatic juice into the bile duct or by biliary infections . We have previously reported that LPC causes cytotoxicity through the induction of apoptosis and induces oxidative DNA damage by reactive oxygen species (ROS) in cholangiocytes. Furthermore, LPC causes cellular senescence with the induction of senescence‐associated secretory phenotype (SASP) .…”
Section: Introductionmentioning
confidence: 99%